The first experience of using {99m}Tc-Al[2]O[3]-based radiopharmaceutical for the detection of sentinel lymph nodes in cervical cancer patients; AIP Conference Proceedings; Vol. 1760 : Physics of Cancer: Interdisciplinary Problems and Clinical Applications 2016 - Sinilkin I. G. Ivan Gennadjevich; Chernov V. I. Vladimir Ivanovich; Lyapunov A. Yu.; Medvedeva А. А. Anna Aleksndrovna; Zelchan R. V. Roman Vladimirovich; Chernyshova A. L.; Kolomiets L. A. (2016, 2016)
Title screen